ANALYSIS ON THE IMPACT OF WONDERFUL INDONESIA BRAND EQUITY TOWARDS FOREIGN TOURISTS’ INTENTION TO VISIT INDONESIA (A STUDY AMONG ASEAN RESIDENCE) - SALSABILA RIZKYA FERANDINAL (Jurnal Ilmiah Mahasiswa FEB, 2018)
This research aims to discover the impact of Wonderful Indonesia Brand Equity (BrandImage, Brand Association, Brand Awareness, and Perceived Quality) Towards Foreign TouristIntention to visit Indonesia with the study among ASEAN Foreigners. The type of this researchis the explanatory research, which explains the relationship and the influence between onevariable and another through hypothesis testing. This research collected sample of 250respondents where the survey was conducted through an online questionnaire. The sample ofthis research consisted of the respondents who were ASEAN residence and recognizeIndonesia's branding, which is Wonderful Indonesia. The data analysis used in this researchwas the Multiple Linear Regression Analysis and the hypothesis testing using the t-test whichis processed through the SPSS software. From the results of testing four hypotheses, it can beconcluded that the variable of Brand Image, Brand Association, Brand Awareness, andPerceived Quality have significant positive influence on the intention to visit Indonesia. Thisresearch implied that proper maintenance of the Brand Equity of Wonderful Indonesia wouldincrease the consumers' intention to visit Indonesia.Keywords: Wonderful Indonesia, Brand Equity, Brand Image, Brand Association, BrandAwareness, Perceived, Consumers' Intention.